1992
DOI: 10.1159/000227088
|View full text |Cite
|
Sign up to set email alerts
|

Altered Pattern of Lipid Metabolism in Patients with Lung Cancer

Abstract: Cholesterol distribution in tumoral tissues and lipid composition in the plasma compartment were determined in patients affected by different histologic types of lung cancer. The results showed that tumoral lung tissues contained 2-fold more total cholesterol and 3.5-fold more esterified cholesterol than normal lung tissues. In the patients the alterations in intracellular cholesterol were also associated with peculiar changes in cholesterol distribution in the plasma compartment. Serum high-density lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 11 publications
4
38
0
Order By: Relevance
“…A direct relationship between breast carcinoma and cholesterol metabolism has not been confirmed yet. However, this is not the case in the carcinoma of the colon and lung and in haematological neoplasia, where decrease in its serum concentration has been confirmed by several authors (Dessi et al 1992;Rose et al 1974;Spiegel et al 1982). In our experiment, no changes in the serum lipids in the carcinogen (NMU)-influenced animals were observed.…”
Section: Discussionsupporting
confidence: 61%
“…A direct relationship between breast carcinoma and cholesterol metabolism has not been confirmed yet. However, this is not the case in the carcinoma of the colon and lung and in haematological neoplasia, where decrease in its serum concentration has been confirmed by several authors (Dessi et al 1992;Rose et al 1974;Spiegel et al 1982). In our experiment, no changes in the serum lipids in the carcinogen (NMU)-influenced animals were observed.…”
Section: Discussionsupporting
confidence: 61%
“…Case-control studies of newly diagnosed lung cancer have shown that HDL-cholesterol levels are reduced in lung cancer cases relative to levels observed in the control groups [7][8][9][10]. This association was found to be independent of type and stage of lung cancer [7], but not all adjusted for smoking or other confounders.…”
Section: Introductionmentioning
confidence: 92%
“…[41][42][43][44][45] Crucially, when examined, many such defects correlate with the degree of inflammatory activity in these disease processes. These observations support the notion that common mechanisms link immune dysregulation and metabolic dysfunction across a range of diseases that share common cellular and molecular effector pathways.…”
Section: Evidence Of Similar Metabolic Perturbances In Other Chronic mentioning
confidence: 99%